Pengaruh Likuiditas Terhadap Kebijakan Dividen pada Perusahaan Manufaktur Yang Terdaftar Di Jakarta Islamic Index 70 (JII 70) Periode 2018-2023 - Maulina, Andini; Badina, Tenny; Fatoni, Ahmad (Jurusan Akuntansi Politeknik Negeri Padang, 2025)
This research aims to determine the liquidity variables using several indicators, namely the current ratio, cash ratio, and quick ratio, in their influence on the dividend payout ratio as an indicator of dividend policy in manufacturing companies listed on the Jakarta Islamic Index 70. The population in this study consists of manufacturing companies listed on the Jakarta Islamic Index 70 for the period 2018-2023. This is a quantitative research type utilizing secondary data. Sample selection was done through purposive sampling, and the data processed in this study are panel data from 9 companies as research samples, with a total of 54 data points. The analytical method employed is multiple linear regression analysis using EViews 9 software. The research results indicate that the current ratio has a positive and significant effect on dividend policy, while the cash ratio has a negaitive and significant effect on dividend policy. However, the quick ratio has appositive and significant effect on dividend policy in manufacturing companies listed on the Jakarta Islamic Index 70.